2018
DOI: 10.1177/1539449218813702
|View full text |Cite
|
Sign up to set email alerts
|

Competence and Satisfaction in Occupational Performance Among a Sample of University Students: An Exploratory Study

Abstract: Success at university may be influenced by concerns with occupation and occupational performance. To understand occupations of concern and occupational performance among a sample ( N = 144) of university students in the Midwest United States, the Canadian Occupational Performance Measure was administered. Socially related ( n = 103), academic-related ( n = 75), and work-related ( n = 64) occupations were the three most frequently reported occupational concerns. Time management ( n = 79) was the most frequent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Our findings indicated that nomophobic students experience sleep problems. This is consistent with another recent study evaluating the occupational performance difficulties of university students, in which sleep was the most problematic occupation (Keptner and Rogers, 2019). Therefore, occupational therapists who work with individuals that have sleep problems should keep nomophobia level in mind as a confounding factor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicated that nomophobic students experience sleep problems. This is consistent with another recent study evaluating the occupational performance difficulties of university students, in which sleep was the most problematic occupation (Keptner and Rogers, 2019). Therefore, occupational therapists who work with individuals that have sleep problems should keep nomophobia level in mind as a confounding factor.…”
Section: Discussionsupporting
confidence: 93%
“…Keptner and Rogers (2019) stated that university students experience more problems in their academic occupations. Similar to their findings, the students in our study sample reported having problems in academic occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, the non-PMDD group also reported problems related to relaxation and enjoyment. Consistent with our findings, a study evaluating occupational competence and satisfaction among university students showed that social participation was their greatest concern (Keptner and Rogers, 2019). These results showed that independent from PMDD symptoms, university students may experience relaxation and enjoyment problems.…”
Section: Discussionsupporting
confidence: 91%
“…Occupational competence includes participating in a variety of occupations to meet the standards expected of one's valued roles in order to sustain a pattern of occupational behavior that is meaningful and satisfying (Taylor, 2017). A study by Keptner and Rogers (2019) evaluating occupational competence and satisfaction among university students showed that social, academic, and work-related occupations were the most frequently reported occupations of concern and that time management was the students' most common personal concern.…”
Section: Introductionmentioning
confidence: 99%
“…It is important for university students to feel competent in their chosen vocation, as this buffers against negative affect (Keptner & Rogers, 2019), such as stress levels (Partido & Owen, 2020), which can in turn impact academic performance (Larson et al., 2016). PSC has also been linked to increased MIL (Demirbaş‐Çelik & Keklik, 2019).…”
Section: Introductionmentioning
confidence: 99%